ANALISIS TINGKAT KENYAMANAN TERMAL MENGGUNAKAN METODE TEMPERATURE HUMIDITY INDEX SERTA KAITANNYA DENGAN KEBERADAAN RUANG TERBUKA HIJAU DI KOTA SURABAYA - Astuti, Diah Novita (Journal of Industrial Process and Chemical Engineering (JOICHE), 2024)
Comfort conditions based on climatology parameters can be considered the comfort level of population in an area. Development in Surabaya area over the past few years has inevitably led to a shift in the function of green land into new buildings, especially residential and industrial ones. This indicated an effect on the condition of thermal comfort due to an increase in surface temperature. Therefore, calculations are carried out to determine the thermal comfort index in Surabaya and spatial analysis to see its distribution. Remote sensing using Landsat imagery is carried out to determine the classification and distribution of vegetation, buildings and water bodies. With overall accuracy about 93%, this land cover of Landsat data is considered good enough to represent the current state of land cover in Surabaya. The results show that there has been a significant change in land cover in almost a decade (2013-2021). The comfort level is best seen at the beginning of the research year (2013) and the lowest one is seen in 2016. Based on these two data, it can be seen that there is a link between the decrease in the quality of the thermal comfort level and the availability of green open spaces. Several things affect the thermal comfort conditions in Surabaya, i.e. geographical conditions, global climate anomaly conditions and the availability of vegetation stands or green open spaces.